Determinant Analysis of Public–Private Partnership in Russia - Lukmanova, Inessa Galeyevna; Mishlanova, Marina Yuryevna (International Journal of Economics and Financial Issues, 2015)
The subject of study in this article is the phenomenon of public-private partnership (PPP). The purpose of the study is to analyze the Russian type of public-private partnership on the basis of qualitative analytical method. The authors put forward the following hypothesis: the application of the method of determinant analysis presented in this article and the results of testing this method increase the validity of managerial decisions in the field of public-private partnership. To achieve the goal of research, the method of determinant analysis is substantiated in this article – the identification of the factor and resulting clusters of the subject of study. On the basis of this method, the formula of the basic characteristic of a public-private partnership is defined; the evolutionary, object-subject, subjective, environmental, formal and methodological determinants are revealed. Concept analysis allowed to justify the development of the market of public services as a social and economic result of the public-private partnership. The formation of the supply and demand in the social and transport infrastructure was fragmentarily considered. In the subjective analysis, the interests of the actors were identified and determinants of consumers of public services were allocated. The authors of the article identified the factor clusters of the environment and suggested ways to improve the assessment of development of the public-private partnership. In result of the research of the methodology determinant, it was suggested to extend the method of the public comparator to evaluate PPP projects. The results of the determinant analysis allowed to determine a comprehensive model for assessing the condition and development of the public-private partnership. To identify the functional request of the super-system, the analysis at the macro level was carried out and the PPP model was identified as a determinant of state administration. The article substantiates that the results of study using the determinant analysis will allow to unlock the potential of public-private partnerships as a determinant of new state administration in modern realities. Keywords: determinant analysis, determinant, public-private partnership (PPP), PPP project, infrastructure, market for public services, evaluation of PPP project, public comparator. JEL Classifications: D24, G21, P26